East-West Demographic Divide in the EU: A Regional Overview - Marko Galjak (Stanovništvo)
The goal was to examine demographic differences between former communist regions and other regions of the EU. Besides providing a regional overview of EU’s demographic differences, we question whether the subnational approach offers any new insights into the East-West divide. This cross-sectional study was conducted on 1,155 EU’s NUTS3 regions from 2014. These regions are grouped in two groups: regions that were part of a communist country, and other regions. Mortality, fertility and age structure indicators were tested between the two groups of regions. GDP/c was used to control for differences in economic development by segmenting the regions into tree brackets: low, medium, and high. The differences were then tested for each indicator. Regional variation within countries for each indicator was also assessed. The gaps exist at regional level and are the widest with mortality and fertility schedule, regardless of GDP/c. Former communist regions on average tend to be slightly younger. Analysis of regional variation showed that subnational approach was warranted when studying East-West demographic disparities, especially when it comes to fertility schedule.